A Swedish Perspective on Research Ethics Review - Hans Thulesius (Grounded Theory Review: An International Journal)
The most famous Swedish example of unethical research is the 1947-1951 Vipeholm sugar trial (Krasse, 2001). Several hundred intellectually and mentally challenged persons at the Vipeholm institution were for years given an excess amount of sugar, mostly in the shape of candy. This resulted in caries that totally ruined the teeth of 50 persons. Of course participants did not give informed consent. Yet, at the time the research was not considered unethical. At least there was no debate about it.